(untitled) (Fiep Bulletin - online, 2014)
Introduction: The natural process named aging has been increased over the last years. We have considered an old person who is more than 60 year old. Objective: The objective this study was evaluated variables in elders submitted to individualized physical training. Methodology: The study’s sample was composed by 18 elders (n=18), all volunteers, with minimum age of 60 indeed. For the measure of the corporal mass and height the following instruments were used: Filizola® balance with 150Kg full capacity and 100Kg sensibility. The individual was without any shoes and with only underwear. The anthropometric scale fixed on the balance, with the individual stand still on your feet, eyes fixed on a horizontal axis parallel to the ground (Frankfurt line). For the fat percentage measure a corporal composition analysts machine by bipolar bio impedance mark Omreon® (USA) has been utilized. To measure the arterial pressure a sphygmomanometers Becton Dicnson; stethoscopes Rappaport - Premium has been utilized. To measure the muscular strength a manual digital dynamometer TAKEL (Japan) has been utilized. To measure the quality of life a questionnaire made by the World Health Organization (WHO) - WHOQOL-OLDyear 2007- has been utilized. The individuals has been received an individualized physical training with concentric muscular work and eccentric for the arms and legs, through cardio and muscular strength exercises. The training program was 1 year and 2 months long, with 2 sections per week with 60 minutes long each. Resultados e Conclusão: De todas as variáveis investigadas neste estudo, concluiu-se que houveram melhoras em 86% das variáveis investigadas, sendo que somente uma (IMC) não houve modificação. O %G do grupo foi classificado como“MUITO RUIM” (FERNANDES FILHO, 2003) e o IMC como “NORMAL” (OMS, 2007). Houveram melhoras nos níveis pressóricos, pois obteve uma queda de quase 10 mmHg da PAS e PAD, sendo de grande importância para a diminuição dos riscos de doenças cardiovasculares, sendo classificados como NORMOTENSOS (A.H.A, 2003). Nas médias de freqüência cardíaca tiveram uma queda de 12 bpm, colaborando com isso para a melhoria na disposição física para executar exercícios e nos afazeres da vida diária. Tanto nos membros superiores direito quanto esquerdo o grupo obteve um ganho de apreensão manual médio de 7Kgf, demonstrando ganho de força muscular. Quanto a variável qualidade de vida, o grupo esta classificado como “SATISFATÓRIO” (OMS, 2007). Constatando assim que após 12 meses, de programa de exercício físico individualizado, houve melhoria nos aspectos cardiovascular, pulmonar, muscular, e na qualidade de vida desses idosos melhorando sua autonomia funcional.